EUTHYROID GOITER AS RISK FACTOR OF PERINATAL COMPLICATIONS - S.Y. Kosilova (Bukovynian State Medical University, 2019)
The spread of thyroid diseases among women of fertile age are constantly increasing. The frequency of euthyroid goiter occupies one of the first places among the pregnant and constitutes from 30% to 40% according to the data of various authors. At the same time, it has an unfavorable influence on the health of a future mother and it is dangerous for the development of the fetus and newborn. In addition, pregnancy itself can affect the development of the given pathology. Interrelation of these processes is not completely studied. Clinical-statistical analysis of the course of pregnancy, labor and newborn state among 50 women with euthyroid goiter has been conducted. The obtained results confirm that euthyroid goiter changed the indices of maternal hemodynamic leading to disorders of the uterine-placental blood circulation and development of placental dysfunction. The results of investigation testify about complicated flow of pregnancy (80% of cases) and labor (88% cases). The examination found that the lower level of free thyroxin of mother correlated with the lower scale evaluation of the fetus. Results of histological examinations of placentas interpret thyroid pathology as the risk factor promoting the development of chronic placental dysfunction.